Analisis dan Perancangan Interoperabilitas Data Pemonitoran SPM (Standar Pelayanan Minimal) Bidang Kesehatan dengan Web Services - Farid Mahmudi (Poltekkes Kemenkes Semarang, 2023)
System interoperability is a key factor in the transformation of the minimum service standards (SPM) reporting system in the health sector. This article presents an in-depth analysis to design an Application Programming Interface (API) model that aims to increase the effectiveness of sending and reporting SPM data from primary health facilities under the district health office. Through analytical studies, we identified system interoperability needs at the district health department level, including aspects such as electronic medical record (EMR) data formats, minimum service standards, and patient identification systems. One of the main challenges is the diversity of data formats and sources that must be integrated. Based on this analysis, we designed an API specifically designed to facilitate the exchange of important data related to reporting minimum service standards in the health sector. The resulting API follows the principles of RESTful architecture, prioritizing scalability, flexibility, and security. API specifications include nationally recognized data standards for health reporting as well as stringent authentication and authorization systems to protect sensitive data. Initial implementation and testing results show that the proposed API successfully connects diverse health reporting systems with high effectiveness. Evaluation of API performance through measuring response time and resource usage indicates adequate performance for use in a production environment. Through the design of this API, it is hoped that it can increase interoperability between minimum service standard reporting systems in the health sector, reduce data duplication, and speed up the reporting process. The conclusions of this study underscore the important role of APIs in supporting healthcare quality, data-driven decision-making, and more efficient integration of medical systems.